Hyaluronic acid-fabricated nanogold delivery of the inhibitor of apoptosis protein-2 siRNAs inhibits benzo[a]pyrene-induced oncogenic properties of lung cancer A549 cells. (19th February 2015) - Lin, Chung-Ming; Kao, Wei-Chien; Yeh, Chun-An; Chen, Hui-Jye; Lin, Shinn-Zong; Hsieh, Hsien-Hsu; Sun, Wei-Shen; Chang, Chih-Hsuan; Hung, Huey-Shan
Abstract: Benzo[ a ]pyrene (BaP), a component of cooking oil fumes (COF), promotes lung cancer cell proliferation and survival via the induction of inhibitor of apoptosis protein-2 (IAP-2) proteins. Thus knockdown of IAP-2 would be a promising way to battle against lung cancer caused by COF. Functionalized gold nanoparticle (AuNP) is an effective delivery system for bio-active materials. Here, biocompatible hyaluronic acid (HA) was fabricated into nanoparticles to increase the target specificity by binding to CD44-over-expressed cancer cells. IAP-2-specific small-interfering RNA (siRNAs) or fluorescein isothiocyanate (FITC) were then incorporated into AuNP-HA. Conjugation of IAP-2 siRNA into AuNPs-HA was verified by the UV–vis spectrometer and Fourier transform infrared spectrometer. Further studies showed that AuNP-HA/FITC were effectively taken up by A549 cells through CD44-mediated endocytosis. Incubation of BaP-challenged cells with AuNP-HA-IAP-2 siRNAs silenced the expression of IAP-2, decreased cell proliferation and triggered pronounced cell apoptosis by the decrease in Bcl-2 protein and the increase in Bax protein as well as the active form of caspases-3. The BaP-elicited cell migration and enzymatic activity of the secreted matrix metalloproteinase-2 were also substantially suppressed by treatment with AuNP-HA-IAP-2 siRNAs. These results indicated that IAP-2 siRNAs can be efficiently delivered into A549 cells by functionalized AuNP-HA to repress the IAP-2 expression and BaP-induced oncogenic events, suggesting the potential therapeutic application of IAP-2 siRNA or other siRNA-conjugated AuNP-HA composites to COF-induced lung cancer and other gene-caused diseases in the future.